Edible Ornamental Landscaping Guide for North-Central Florida - Amanda Marek; Mark Bailey; Gail Hansen (EDIS)
Well-designed edible ornamental landscapes, also called foodscapes, provide landowners with aesthetically pleasing, multipurpose gardens that provide food, color, and cover year-round. The purpose of this new 15-page publication is to guide Floridians on how to design, install and maintain their edible ornamental landscape using reliable plants suitable for north-central Florida and the best management practices of Florida-Friendly Landscaping™. Written by Amanda Marek, Mark Bailey, and Gail Hansen, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep618